Instrumented climbing holds and performance analysis in sport climbing - Fuss, F. K.; Niegl, G. (Sports Technology, 2008)
In three different events (national climbing Championship, sport climbing world cup, and training session), one hold was instrumented with two 3-D force transducers. Subsequently, the mechanical parameters of climbing were defined and analyzed, and the force vector diagrams visualized for quantification of performance.The more experienced a climber is, the smaller the contact force, the shorter the contact time, the smaller the impulse, the better the smoothness factor, thehigher the friction coefficient, the more continuous the movement of the center of pressure (in specific holds), and the smaller the Hausdorff dimension (less chaotic force time graph). The Hausdorff dimension correlates highly with all other parameters and with the appearance of the vector diagrams, and is thus suited to serve as the most important performance parameter. Training improves the mechanical parameters. The measurement and analysis of mechanical parameters and their visualization in terms of force vector diagramsare a useful tool for quantifying the performance of a climber on a specific instrumented hold.